Role of an Online Skill-Based Mindfulness Program for Healthcare Worker's Resiliency During the COVID-19 Pandemic: A Mixed-Method Study - Kim, Soyeon; Crawford, Jennifer; Hunter, Sarah (Frontiers in Public Health, 2022)
The COVID-19 pandemic has highlighted the mental health care needs of health care workers. The primary aim of this study was to explore the effects of an online mindfulness program on resiliency in health care workers during the pandemic using a mixed-methods approach. An online 4-week mindfulness program was delivered to healthcare workers (N=130) in Ontario, Canada. Resiliency was assessed at 3-time points (i.e., pre, post, and 1-month follow-up), and the mindfulness program's efficacy on resiliency was analyzed using linear regression. Semi-structured interviews (N=10) were conducted to substantiate their experiences. Healthcare workers' resiliency significantly increased after the mindfulness program compared to the baseline, maintaining the effect after one month in both unadjusted and adjusted regression models. These findings were further bolstered by the positive experiences shared by participants highlighting the program's efficacy on empathy and resiliency. Evidence suggests that mindfulness is associated with promoting resiliency in healthcare workers and may be an important strategy to promote resiliency in this population.